Polyhymnia’s Agent : Musical Humanism, Exordial Rhetoric, and the Veneration of Antiquity in the Works of Michael Praetorius (1571–1621) - Halonen, Miikkael (Hymnologian ja liturgiikan seura, 2024)
The Middle-German composer Michael Praetorius (1571–1621) has been considered a cultural agent between the Renaissance and Baroque periods, as well as between southern and northern Europe (Forchert 1959: ix–x; 2021; Rode-Breymann & Spohr 2011: 15; Limbeck, Schmitt & Wirth 2022: 13). Even if this is true, the viewpoint has hitherto concerned transferring only musical styles and practices. Praetorius’s agentive role over time and place is still a more multi-faceted phenomenon than one might assume. His works, both writings and compositions, also reflect extramusical, educational, and ethical dimensions. I argue that one can find certain ideals of historical continuity and inevitable imitation of ancient things (res antiquae) in Praetorius’s writings. In other words, these ideals have to do with the ethos of sincere veneration of antiquity, not only in musical practices but in all literary culture, both ecclesiastical and civic life. His literary, poetic, and rhetorical ideals reach far, from ancient Mount Parnassus to the early modern organ loft of Wolfenbüttel’s Court Chapel. --
Keywords: antiikki; retoriikka; musiikki; musiikkifilosofia; liturginen musiikki